GEOCHEMISTRY OF THE UPPER CRETACEOUS SHALES FROM GOMBE FORMATION, GONGOLA BASIN, UPPER BENUE TROUGH, NIGERIA: IMPLICATIONS FOR PROVENANCE AND TECTONIC EVOLUTION - Ogbesejana, Abiodun B.; Sabo, Sulaiman Auwal; Alisi, Ikechukwu Ogadimma; Egwu, Augustine C.; Odusina, Babatope Oluseun (FUDMA Journal of Sciences, 2024)
The Gombe Formation, situated in the northeastern region of Nigeria, contains shales in addition to various sedimentary lithologies such as sandstones, mudstones, and coals. Nonetheless, the comprehensive geochemical analyses of the major oxides of these shales remain inadequately documented to date. The current study aimed to elucidate the geochemical significance of major oxides of the shales from the Gombe Formation in the Upper Benue Trough, Nigeria, using x-ray fluorescence spectrometry (XRF) within the context of provenance, tectonic settings, and paleosalinity. The average concentration of the major oxides ranged from 0.02 to 34.93 % in the shales. Among the twenty-four (24) major oxides detected, the shales exhibit elevated concentrations of SiO2, with Al2O3>Fe2O3>SO3>MgO>CaO>SrO>BaO>K2O>TiO2>Sb2O3>CeO2>MnO, whereas the remaining oxides exhibited low concentrations. This observation implies that the shales were predominantly composed of quartz minerals and deposited in marine environments. The relatively high concentrations of Fe2O3 (with an average value of 3.36 %) and MgO (with an average value of 2.48 %) in the samples suggest that the source rocks were likely of a mafic to ultramafic nature. The values of Al2O3/TiO2 and SiO2/Al2O3 in the shales ranged from 1.75 to 11.02 and 6.95 to 38.44, respectively. These values indicated their derivation from a mixture of felsic igneous and mafic igneous rocks and mixed compositional maturity in proximity to the active continental margin. This study demonstrated that major oxides serve as a robust tool for assessing the provenance and tectonic characteristics of the shales from the Gombe Formation within the Gongola Basin, Nigeria.
Keywords: Major oxides; Provenance; Tectonic settings; Gombe formation; X-ray fluorescence spectrometry